Kinematic analysis of seven-degree-of-freedom exoskeleton rehabilitation manipulator. (18th January 2022) - Tang, Gang; Sheng, Jinqin; Wu, Chuan; Wang, Dongmei; Men, Shaoyang
This article analyzes the forward kinematics and inverse kinematics of the seven-degree-of-freedom exoskeleton rehabilitation manipulator. Denavit–Hartenberg coordinates are used to model the forward kinematics, and the working space of the end effector of the manipulator is analyzed according to the joint motion range of the human arm. In the inverse solution of the seven-degree-of-freedom exoskeleton rehabilitation manipulator, the self-motion angleϕ of the elbow is used. The minimum energy standard is used to calculate the self-motion angleϕ . The minimum energy mainly includes the gravitational potential energy of the upper limbs and the elastic potential energy stored in the muscles. Thus, the inverse solution formula of the seven-degree-of-freedom exoskeleton rehabilitation manipulator is derived. When calculating the angleθ 4, an auxiliary parameter is introduced to solve the self-motion manifold of the manipulator. Finally, the theoretical derivation and verification of the forward and inverse kinematics are carried out in this article, and through analysis of the results, it is concluded that the inverse kinematics of this article has some limitations but the theory of inverse kinematics is feasible.